Atasi Tantangan: Memahami Pentingnya Uji Insolvensi dalam Kepailitan di Indonesia - Sunur, Fransiskus Stefan (Universitas Medan Area, 2024)
This article aims to analyze the urgency of implementing an insolvency test in Indonesia's Bankruptcy Law using a comparative method with other countries. The focus is on the differences in bankruptcy regulations, particularly regarding the insolvency test. The methodology includes legislative and comparative approaches, with data collected through literature studies to gather relevant primary and secondary legal materials. The research findings indicate that the insolvency test has been effectively used in the United States in cases such as Enron Corporation and Lehman Brothers Holding. The United Kingdom has also applied the insolvency test in handling the bankruptcy of MG Rover Group Ltd., as has Japan in the case of Kanebo. Based on the experiences of these countries, implementing the insolvency test in Indonesia could enhance fairness and effectiveness in determining a debtor's bankruptcy status and minimize the misuse of the bankruptcy institution. A comparative approach with countries like the United States, the United Kingdom, and Japan demonstrates that the bankruptcy system and procedures can be improved by adopting the insolvency test. This test involves not only court decisions but also an analysis of a company's ability to pay its creditors. In conclusion, implementing the insolvency test in Indonesia could increase legal certainty and protect the interests of all parties involved in the bankruptcy process, as well as boost investor confidence. However, the main challenges include the lack of a clear legal basis and high costs due to the need for financial experts to conduct the analysis.